A systematic literature review of Covid-19 impact to SME’s adoption of e-commerce - Cheong, Jia Qi; Noor Faziedah Chun Lee; Kasim Md Mansur (Universiti Malaysia Sabah, 2020)
This paper presents a systematic review of existing literature analyzing the E-commerce SME. The objectives of this paper is to provide an insight through a systematic literature review of latest research evidence on e-commerce adoption among small to medium-sized enterprise (SMEs) with a focus in Malaysia. It is necessary to address our concern because of this adoption in order help SME digital solutions. This paper could be very helpful for researchers, investors, policy-makers and whoever interested in the impact to SME"s adoption of e-commerce in Malaysia development.